2018
DOI: 10.11648/j.ajns.20180705.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urinary Incontinence on Quality of Life and Self Esteem of Postmenopausal Women

Abstract: Background: Urinary incontinence (UI) is the debilitating condition with impact on physical and psychological aspect of life with consequent effect on the quality of life (QoL). Aim of the study was to determine the effect of urinary incontinence (UI) on quality of life and self esteem of postmenopausal women. A descriptive design was adopted to fulfil the aim of this study. The study was conducted at obstetric & gynaecological outpatient clinic and Urological outpatient clinic at Benha University Hospital. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
3
17
1
Order By: Relevance
“…There have been few studies about the quality of life in postmenopausal women with different types of urinary incontinence. 9,26 Consistent with our results, some studies reported low quality of life scores in women with stress incontinence. 5,27 Although sample sizes were different, the results were similar and in line with the present one.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There have been few studies about the quality of life in postmenopausal women with different types of urinary incontinence. 9,26 Consistent with our results, some studies reported low quality of life scores in women with stress incontinence. 5,27 Although sample sizes were different, the results were similar and in line with the present one.…”
Section: Discussionsupporting
confidence: 92%
“…8 Also, its prevalence among postmenopausal women varies between 8% and 56%, depending on the type of study. 5 About 9%–39% of women >60 years report daily urine leakage 9 ; it is mainly due to thinning of the bladder mucosa and urethra because of estrogen deficiency in these women. 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Incontinence is negatively affected by women's sexual function and relationships with their partners. 21,[24][25][26] Thus, women's low self-confidence feeling is increased. 24,25 Studies have been determined that increase in UI severity negatively affected the quality and frequency of sexual intercourse.…”
Section: Physiological Modementioning
confidence: 99%
“…In this study, women acknowledged that their self-confidence decreased with urinary dysfunctions aggravation. Urinary incontinence may lead to emotional distress, isolation from society, and decreased self-esteem in older women, because of the experience of incontinence in public and an unpleasant feeling of embarrassment due to wetness and the smell of urine [29,30].…”
Section: Psycho-emotional Consequencesmentioning
confidence: 99%